+0  
 
0
36
1
avatar

8.(-2/3)^2-12.(3/4)^2+(-1)^2020

 Aug 30, 2020
 #1
avatar+121 
0

Assuming you want us to simplify:

\(\)(\(\frac {-2}{3})^{2} -12(\frac {3}{4})^2 + -1^{2020} \implies \frac {4}{9} - 12 (\frac {9}{16}) + 1 \implies \frac 49 - \frac 94 + 1 \implies - \frac {29}{36} \implies -0.80 \overline {5}\)

 

If this did not render, please see the file attached. Sorry, it is a little low resolution. (The LaTeX doesn't always work when not logged in.)

 

Hope this helps!

 

 Aug 30, 2020
edited by Nacirema  Aug 30, 2020

41 Online Users

avatar
avatar